Rural hospitals are not associated with worse postoperative outcomes for colon cancer surgery. Issue 3 (20th May 2021) - Lansing, Shan S.; Diaz, Adrian; Hyer, Madison; Tsilimigras, Diamantis; Pawlik, Timothy M.
Abstract: Purpose: We sought to determine whether colorectal cancer surgery can be done safely at rural hospitals. The current study compared outcomes among rural patients who underwent colon resection at rural and nonrural hospitals. Methods: Medicare beneficiaries who underwent colon resection for cancer between 2013 and 2017 were identified using the Medicare Inpatient Standard Analytic Files. Patients and hospitals were designated as rural based on rural‐urban continuum codes. Risk‐adjusted postoperative outcomes and hospitalization spending were compared among patients undergoing resection at rural versus nonrural hospitals. Results: Among 3, 937 patients who resided in a rural county and underwent colon resection for cancer, mean age was 76.3 (SD: 7.1) years and 1, 432 (36.4%) patients underwent operative procedure at a rural hospital. On multivariable analyses, no differences in postoperative outcomes were noted among Medicare beneficiaries undergoing colon resection for cancer at nonrural versus rural hospitals. Specifically, the risk‐adjusted probability of experiencing a postoperative complication at a nonrural hospital was 15.4% (95% CI: 14.1%‐16.8%) versus 16.3% (95% CI: 14.2%‐18.3%) at a rural hospital (OR 1.08, 95% CI: 0.85‐1.38); 30‐day mortality (nonrural: 2.9%, 95% CI: 2.2‐3.6 vs rural: 3.5%, 95% CI: 2.4‐4.5) was also comparable. In addition, price standardized, risk‐adjusted expenditures were similar at nonrural (18, 610, 95% CI: 18, 037‐19, 183) and rural (19, 010, 95% CI: 18, 630‐19, 390) hospitals. Conclusion: Among rural Medicare beneficiaries who underwent a colon resection for cancer, there were no differences in postoperative outcomes among nonrural versus rural hospitals. These findings serve to highlight the importance of policies and practice guidelines that secure safe, local surgical care, allowing rural clinicians to accommodate strong patient preferences while delivering high‐quality surgical care.